2017
DOI: 10.1097/cad.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

YM155 induces apoptosis in p53-deficient T-acute lymphoblastic leukemia cells independent of survivin inhibition

Abstract: T-acute lymphoblastic leukemia (T-ALL) is an aggressive hematological cancer that arises from the malignant transformation of T-cell progenitors. Despite the significant progress in current treatment, challenges remain the lifelong morbidity after current chemotherapy regimens and postrelapse survival. In addition, patients with T-ALL have inferior outcomes compared with those with B-cell precursor; consequently, novel therapeutic approaches are still necessary to improve the outcome in this cohort. YM155 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…These results suggest that survivin cannot be the only target of YM-155, and the observed sensitizing effect should be survivin-independent [32]. The same surprising survivin expression-independent effect of YM-155 was also reported for p53-deficient T-acute lymphoblastic leukemia (ALL) [33] and renal cell carcinoma [34]. Another study evaluating the radiosensitization effects of YM-155 on esophageal squamous cell carcinoma reported that the treatment abrogated the radiation-induced G2/M arrest [35].…”
Section: Radio-and Chemosensitizing Effects Of Ym-155 Are Survivin-independentsupporting
confidence: 59%
“…These results suggest that survivin cannot be the only target of YM-155, and the observed sensitizing effect should be survivin-independent [32]. The same surprising survivin expression-independent effect of YM-155 was also reported for p53-deficient T-acute lymphoblastic leukemia (ALL) [33] and renal cell carcinoma [34]. Another study evaluating the radiosensitization effects of YM-155 on esophageal squamous cell carcinoma reported that the treatment abrogated the radiation-induced G2/M arrest [35].…”
Section: Radio-and Chemosensitizing Effects Of Ym-155 Are Survivin-independentsupporting
confidence: 59%
“…27 For instance, a range of plant extracts have been tested by this method to isolate components with potent inhibitory activity for further tests, 28,29 and YM155, an antitumor imidazolium compound and potent inhibitor of Survivin, was tested on a variety of human cancer cell lines, including T-acute lymphoblastic leukemia (T-ALL). 30 The initial screening on HTLV-1-infected cell line (MT-2) led us to select eight compounds (02, 05, 06, 13, 15, 21, 22 and 25) (Figure 2) for further studies as they significantly reduced the metabolic activity of the cells (≥ 70%) in a similar manner to the positive control (ETO). In a follow-up experiment, we investigated whether the selected compounds could interfere in the cell cycle and induce apoptosis of MT-2 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed in tumor and normal cells according to well-established protocols. 40,41 Cells were seeded into 96-well flat-bottom plates at a density of 5 ×10 3 cells well -1 or 1 ×10 4 cells well -1 depending on the cell line. Cell cultures were treated with substances 4 or 5 (concentration range 0-500 µM) for 48 h. Ketoprofen and cisplatin (Sigma-Aldrich, Saint Louis, MO, USA) were used as controls.…”
Section: Cell Viability Assaymentioning
confidence: 99%